middle and high school students, social well-being, threats from social environment, life position, social stratification factors, factor analysis. - Potapova E.A; Zemlyanoy D.A; Kondratyev G.V (Moscow State University of Psychology and Education, 2021)
The study examines certain aspects of the physiological and mental states of students caused by the conditions of social isolation caused by the COVID-19 pandemic and the need to study remotely. 189 respondents (84.6% female, 15.4% male) aged 17 to 27 years were interviewed. The data was collected remotely (using a Google form) between November and December 2020. The following methods were used: the author's questionnaire aimed at evaluating the regime moments, eating habits and physical activity of students, as well as their academic load; the questionnaire "Well-Being, Activity, Mood"; the Beck Depression Inventory; the Spielberger-Hanin anxiety scale. The results showed that in the conditions of distance learning, the lifestyle of a significant proportion of students is characterized by pronounced deviations from the recommended values. Sleep deprivation, an unbalanced diet, a decrease in physical activity - all this, along with a pronounced academic load of medical students, leads to a deterioration in their functional state. A close relationship between the physical and emotional well-being of students was revealed. At the same time, the main predictors of physical well-being are regular physical activity and commitment to a healthy life- style, while emotional well-being is largely determined by the personal characteristics of students and the ability to adapt to a new learning regime.